Properties of Concrete Containing Type-C Fly Ash Under Elevated Temperature - Kencanawati, Ni Nyoman; Murtiadi, Suryawan; Qomari, Lina Sabrina; Zaki, Ahmad (Universitas Muhammadiyah Yogyakarta, 2023)
High temperatures affect the properties of the concrete material. The changes generally depend on the quality of the concrete and the content of added ingredients during concrete mixing. This article examines the strength, weight, and visual changes of normal and high-strength concrete with the addition of class C fly ash (FA) under elevated temperature. FA was added as much as 15% by cement weight in each concrete type. The specimens consisted of four types concrete: normal concrete, normal concrete + FA, high-strength concrete, and high-strength concrete + FA. The fire test was carried out after 45 days curing time for 3 hours with variations in combustion temperature of 500ºC and 1000ºC. Visually, the concrete changes color to yellow-white with micro-cracks after being exposed to a temperature of 500ºC, while at 1000ºC, the surfaces of the concrete turns white, and there are larger and more apparent cracks. Furthermore, adding class C FA to high-strength concrete does affect the fire resistance level because it showed almost the same residual compressive strength after exposure to both elevated temperature of 500°C and 1000°C.